Kontribusi Jenis-jenis Dukungan Sosial terhadap Dimensi-dimensi Psychological Well-Being pada Lansia di Panti âXâ Kota Sukabumi - ., admin (Zenit, 2015)
The purpose of this research is to find out the contribution of the four basic functions of social support to the dimensions of psychological well-being on the elderly that live at Panti “X”Sukabumi. The dimensions of psychological well- being are measured by a modified version of The Ryff Scales ofPsychological Well-Being, based on Ryff„s theory (1995). The functions of social support are measured by using a social support questionnaire that is constructed based on the social support theory of Uchino (2004). The validity process of both instruments is performed by using content validity with 4 experts. The research questionnaire had been distributed to20 elderly that live at Panti “X” Sukabumi. The data were statistically processed by using the statistical multiple regression.Based on the statistical analysis in this research, the conclusions are: An emotional support has a significant contribution to a positive relationship with one another, a tangible/instrumental support has a significant contribution to the environmental mastery, while a companionship support has a significant contribution to the personal growth. It is suggested to examine the relationship or influencial traits of social support and dimensions of psychological well-being. The manager andhead of the boarding arrange activities to increase the intensity of communication of elderly and equip them with facilities to support the health of the elderly.Keywords: Psychological well-being, social support, elderly